2022
DOI: 10.1097/ju.0000000000002425
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological Adverse Events in Prostate Cancer Patients Treated with the Androgen Receptor Inhibitor Apalutamide

Abstract: Purpose: Patients with prostate cancer (PCa) treated with apalutamide frequently develop rash. We aim to characterize apalutamide-related dermatological adverse events (dAEs) and management. Materials and Methods: We assessed 303 patients with PCa treated with apalutamide. DAE frequency and time to onset were calculated and clinicopathological features and management described. Associations between dAE occurrence and clinical trial participation, as well as abiraterone/prednisone exposure were detected using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Indeed, this is not surprising as the evaluation and reporting of AE are more strict within a clinical trial and patients in real-world practice may only refer to the most severe symptoms or these may be underreported if already managed by family doctors or other specialities. 19,20 Our results are similar to the lower frequency of AE found in a similar real-world study by Hussain and colleagues. 21 When analyzing the first therapy administered after apalutamide discontinuation, a predominance of Note: The numerators and denominators per variable adjusted according to the amount of valid data in this study are described in Table S2.…”
Section: T a B L E 1 (Continued)supporting
confidence: 91%
“…Indeed, this is not surprising as the evaluation and reporting of AE are more strict within a clinical trial and patients in real-world practice may only refer to the most severe symptoms or these may be underreported if already managed by family doctors or other specialities. 19,20 Our results are similar to the lower frequency of AE found in a similar real-world study by Hussain and colleagues. 21 When analyzing the first therapy administered after apalutamide discontinuation, a predominance of Note: The numerators and denominators per variable adjusted according to the amount of valid data in this study are described in Table S2.…”
Section: T a B L E 1 (Continued)supporting
confidence: 91%
“…Interestingly, the other AR inhibitor enzalutamide, darolutamine, showed a low rash incidence in clinical trials. This difference may be due to the chemical structure of apalutamide, which has a more reactive 2-cyanopyridine moiety and more readily activates the immune system by increasing lymph node cellularity and T cell and B cell counts ( Drago et al, 2021 ; Pan et al, 2022 ). A published study showed that high apalutamide exposure was significantly associated with skin rash; thus, dose reductions may help prevent dAE recurrence ( Perez-Ruixo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be graded based on the extent of body surface area (BSA) involvement and clinical manifestations. Figure 1 presents further details related to grading criteria and corresponding treatment approaches [18,57] .…”
Section: Uroprecisionmentioning
confidence: 99%
“…In case of improving the rash to grade 1 or returning to baseline, NHT can be resumed with a reduced dose. However, in case of no improvement in the rash, it is advisable to consult with a dermatologist [ 57 ] .…”
Section: Part Ii: Management Strategymentioning
confidence: 99%